The Microeconomics of Market Failures and Institutions An Intermediate Textbook - Teulings, Coen; Huysmans, Martijn (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
XXV, 296 p. 80 illus., 58 illus. in color.